2021
DOI: 10.3233/jad-210128
|View full text |Cite
|
Sign up to set email alerts
|

PRESENILIN 1 Mutations Causing Early-Onset Familial Alzheimer’s Disease or Familial Acne Inversa Differ in Their Effects on Genes Facilitating Energy Metabolism and Signal Transduction

Abstract: Background: The most common cause of early-onset familial Alzheimer’s disease (EOfAD) is mutations in PRESENILIN 1 (PSEN1) allowing production of mRNAs encoding full-length, but mutant, proteins. In contrast, a single known frameshift mutation in PSEN1 causes familial acne inversa (fAI) without EOfAD. The molecular consequences of heterozygosity for these mutation types, and how they cause completely different diseases, remains largely unexplored. Objective: To analyze brain transcriptomes of young adult zebra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 117 publications
3
19
0
Order By: Relevance
“…In our previously published analyses, we found that heterozygosity for most of our EOFAD-like mutations does not result in many differentially expressed genes in young adult brains (as would be expected for modelling a disease that becomes overt in middle age) ( Barthelson et al, 2020b , 2021a , 2021b , 2021c ; Newman et al, 2019 ). Therefore, we performed gene set enrichment analyses (GSEA) to predict which cellular processes were affected by each of the mutations in each experiment.…”
Section: Resultssupporting
confidence: 58%
See 4 more Smart Citations
“…In our previously published analyses, we found that heterozygosity for most of our EOFAD-like mutations does not result in many differentially expressed genes in young adult brains (as would be expected for modelling a disease that becomes overt in middle age) ( Barthelson et al, 2020b , 2021a , 2021b , 2021c ; Newman et al, 2019 ). Therefore, we performed gene set enrichment analyses (GSEA) to predict which cellular processes were affected by each of the mutations in each experiment.…”
Section: Resultssupporting
confidence: 58%
“…We also found evidence for changes to cell-type proportions in both APOE-TR and App NL-G-F mice, a phenomenon that can create the artefactual appearance of gene expression change. We have not observed cell-type proportion differences in 6-month-old or 24-month-old zebrafish ( Barthelson et al, 2020b , 2021a , b , c ; Hin et al, 2020 , 2021 ; ), possibly because of the resistance to damage of the highly regenerative zebrafish brain ( Kroehne et al, 2011 ).…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations